Identifying Telemedicine Services to Improve Access to Specialty Care for the Underserved in the San Francisco Safety Net - Ken Russell Coelho (International Journal of Telemedicine and Applications)
Safety-net settings across the country have grappled with providing adequate access to specialty care services. San Francisco General Hospital and Trauma Center, serving as the city's primary safety-net hospital, has also had to struggle with the same issue. With Healthy San Francisco, the City and County of San Francisco's Universal Healthcare mandate, the increased demand for specialty care services has placed a further strain on the system. With the recent passage of California Proposition 1D, infrastructural funds are now set aside to assist in connecting major hospitals with primary care clinics in remote areas all over the state of California, using telemedicine. Based on a selected sample of key informant interviews with local staff physicians, this study provides further insight into the current process of e-referral which uses electronic communication for making referrals to specialty care. It also identifies key services for telemedicine in primary and specialty care settings within the San Francisco public health system. This study concludes with proposals for a framework that seek to increase collaboration between the referring primary care physician and specialist, to prioritize institution of these key services for telemedicine.